Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Dalam Rumah Tangga di Desa Bandar Khalipah Dusun XI Kec. Precut Sei Tuan Kab. Deli Serdang - Zaini Munawir; Fitri Yanni Dewi Siregar; Raudha Anggraini Tarigan (Pelita Masyarakat, 2022)
Domestic violence is not only physical, but psychological and sexual which can happen continuously. Threats with weapons and death are the biggest risks that can arise if domestic violence is not stopped. Violence against children in the family by their own parents is basically a crime even though the motivation is right. This service aims to find out what forms of violence are experienced by children as victims of domestic violence (DRT) and how are forms of legal protection for children as victims of domestic violence in Bandar Khalipah Village, Dusun XI Kec. Precut Sei Tuan Kab. Deli Serdang. This community service activity is a form of implementation of the collaboration between the Medan Area University and Bandar Khalipah Village, Dusun XI Kec. Precut Sei Tuan Kab. Deli Serdang. This Community Service is carried out for 3 days starting on 09, 10 and 11 November 2021, 14.00 - Finish which consists of planning, preparing and implementing service activities. The conclusion that can be drawn from this activity is the need for special attention to institutions in charge of protecting children such as LPKA, LPAS and LPKS institutions and providing socialization of laws and regulations relating to child protection to all levels of society.